GAMBARAN GAYA HIDUP GENERASI MILLENIAL MUSLIM DALAM NOVEL GENERATION M- YOUNG MOESLIM CHANGING THE WORLD KARYA SHELINA JANMOHAMMED - Novia Sulastri; Erik Candra Pertala; Siska Hestiana (Nusantara Hasana Berdikari, 2022)
In order to understand and provide broader ideas about narrow Islamic stereotypes, it is necessary to refresh and provide publications on Islamic life openly, modern lifestyle that goes hand in hand with Islam. This study wants to see how the lifestyle of the Muslim millennial generation is aimed at understanding the style and pattern of life. This study examines the lifestyle of the Muslim millennial generation and the impact of the Muslim millennial lifestyle from the novel Generation M - Young Moeslim Changing The World by Shelina Janmohammed. This research is intended to uncover, explore and understand the various lifestyles of Muslim millennials and the impact of the lifestyles depicted. The purpose of this study is to describe the life of the Muslim millennial generation and reveal the impact of the Muslim millennial lifestyle. This study uses a descriptive qualitative method in providing a description and providing a clear and useful description to answer the problem. The data of this research were obtained from book sources, namely the novel Generation M -Young Moeslim Changing The World by Shelina Janmohammed as well as articles and homepage sources. In this study, the lifestyles of the Muslim millennial generation described in the novel Generation M - Young Moeslim Changing The World by Shelina Janmohammed were obtained: First, Actualizes (a lifestyle with a high level and high orientation), Second Archievers (hard workers and connoisseurs of results), Third Believers (Centered on religious beliefs, community and national activities), Fourth Experiences (lifestyle that likes new things), Fifth Fulfilled (professional and responsible lifestyle), Sixth Makers (Those who bring influence in a practical way), Seventh Strivers (hard workers but minimum of economy, social, and culture) and Eighth, namely Strugglers (low-income lifestyle). And the impact that occurs due to the lifestyle of the Muslim millennial generation is rational, has careful planning and has a good orientation.